47% OF GRADUATE COURSES IN PHYSICAL EDUCATION NOT PROVIDE THE INFORMATION IN THEIR CURRICULUM WEBSITES (Fiep Bulletin - online, 2011)
From the Website of each Higher Education Institution in Brazil that offers Graduation Programs in Physical Education, the availability of quantified data of the curriculum subjects of Human Physiology, Physiology of Exercise, Nutrition, Sports Nutrition, Football, Futsal, and organize its concentration in the North, Northeast, Midwest, Southeast, South and aggregation in Brazil, discovering that 47% of Graduate Programs in Physical Education do not provide the curriculum data on their respective Websites.
Keywords: website; physical education; curriculum